Status epilepticus from GABABR antibody positive encephalitis due to de novo mixed small cell and adenocarcinoma of the prostate. Issue 11 (30th November 2020) - Kwan, Christopher; Sia, Aaron; O'Gorman, Cullen
Abstract : We present a case study of a 67-year-old man who presented with a new onset of recurrent tonic-clonic seizures. He had tested positive to gamma-aminobutyric acid B receptor antibodies in his blood and cerebrospinal fluid, and subsequent CT imaging and transrectal biopsy confirmed the presence of a locally advanced mixed small cell and Gleason 9 adenocarcinoma of the prostate. His seizures remained resistant to treatment with multiple antiepileptic drugs, including sodium valproate, clobazam, topiramate, carbamazepine, phenytoin and lacosamide. He progressed to status epilepticus, which required intravenous immunoglobulin and steroids, followed by plasma exchange 1 week later. The status epilepticus was refractory and required multiple admissions to the intensive care unit.